An integrated platform for design and numerical analysis of shield tunnelling processes on different levels of detail - Ninić, Jelena; Koch, Christian; Stascheit, Janosch (Elsevier, 2017)
Building and construction information modelling for decision making during the life cycle of infrastructure projects are vital tools for the analysis of complex, integrated, multi-disciplinary systems. The traditional design process is cumbersome and involves significant manual, time-consuming preparation and analysis as well as significant computational resources. To ensure a seamless workflow during the design and analysis and to minimise the computation time, we propose a novel concept of multi-level numerical simulations, enabling the modelling on different Levels of Detail (LoDs) for each physical component, process information, and analysis type. In this paper, we present SATBIM, an integrated platform for information modelling, structural analysis and visualisation of the mechanised tunnelling process for design support. Based on a multi-level integrated parametric Tunnel Information Model, numerical models for each component on different LoDs are developed, considering proper geometric as well as material representation, interfaces and the representation of the construction process. Our fully automatic modeller for arbitrary tunnel alignments provides a high degree of automation for the generation, the setup and the execution of the simulation model, connecting the multi-level information model with the open-source simulation software KRATOS. The software of SATBIM is organized in a modular way in order to offer high flexibility not only for further extensions, but also for adaptation to future improvements of the simulation software. The SATBIM platform enables practical, yet flexible and user-friendly generation of the tunnel structure for arbitrary alignments on different LoDs, supporting the design process and providing an insight into soil-structure interactions during construction.